HUBUNGAN ANTARA DUKUNGAN SOSIAL DENGANKECEMASAN MENGHADAPI DUNIA KERJA PADA FRESHGRADUATES DI KOTA DAN KABUPATEN TEGAL - Nathanael Adin Nugroho Kurniawan; Doddy Hendro Wibowo (Jurnal Riset Psikologi, 2025)
Elevated unemployment rates induce concern in recent graduates regarding their transition into the workforce; nevertheless, social support from their surroundings helps mitigate this anxiety. The objective of the study was to ascertain the correlation between social support and anxiety in connection to the workforce among recent graduates. This study employs quantitative methodologies with a correlational analytic design. The participants comprised 123 recent graduates who had not yet entered the workforce, selected through a purposive sample technique. This study utilized the Social Support Scale (SSS) and the Career Anxiety Scale (CAS) as tools. The findings of this study indicate that social support exhibits a positive and significant link with anxiety related to the workforce among recent graduates (r = 0.653, sig = 0.000). Consequently, it can be inferred that social support does not mitigate anxiety levels among recent graduates.